Reclaiming our humanity: redemption, reimagining, and restorying of the foundations for success of formerly incarcerated African American males - Alexander, Robert Mossi, III (2022)
African American men represent the highest population found in the criminal justice system. Systemic racism contributes to the high recidivism rates of formerly incarcerated Black men. Additional barriers to affordable education, job training, and other services exist for the formerly incarcerated. The purpose of this study was to interview formerly incarcerated African American men and provide a counter-narrative of the foundations for success post-incarceration. This research project explored the narratives of the lived experiences of formerly incarcerated Black men through the lenses of two theoretical frameworks: Black critical race theory and abolitionist theory. Together these frameworks work to shift the narrative around decarcerated Black men. Data were collected via one-on-one interviews with six formerly incarcerated African American men based in California. Six themes emerged from the data: (1) Early educational experiences: The love for learning that was not cultivated; (2) The absence of belonging: Growing up in a traumatic environment incarceration; (3) Incarceration: Building meaningful connections through mentorship, reading, and debating; (4) Post-incarceration: Programs facilitating transition and educational opportunities; (5) Factors that build success: Reactivating the genius inside us, networking, and education; and 6) Recommendations and the foundations for success. The findings of this study highlight the additional barriers that formerly incarcerated African American males encounter during reentry and job placement. Furthermore, the results highlight the urgency of providing culturally relevant mentorship and affordable education, job training, job placement and cross-collaboration between institutes of higher learning and reentry organizations, along with developing increased awareness and understanding of the unique needs of formerly incarcerated African American males. Results from this study offer insight and implications for improving the reentry experiences of African American males in both policy and practice.